Computational models, software engineering, and advanced technologies in air transportation next generation applications - Li, Weigang; Barros, Alexandre de; Oliveira, Ítalo Romani de (Engineering Science Reference, 2010)
"This book disseminates knowledge on modern information technology applications in air transportation useful to professionals, researchers, and academicians"--Provided by publisher.